2018
DOI: 10.2147/ijn.s158536
|View full text |Cite
|
Sign up to set email alerts
|

Curdlan sulfate&ndash;<em>O</em>-linked quaternized chitosan nanoparticles: potential adjuvants to improve the immunogenicity of exogenous antigens via intranasal vaccination

Abstract: IntroductionThe development of ideal vaccine adjuvants for intranasal vaccination can provide convenience for many vaccinations. As an ideal intranasal vaccine adjuvant, it should have the properties of assisting soluble antigens to pass the mucosal barrier and potentiating both systemic and mucosal immunity via nasal administration.MethodsBy using the advantages of polysaccharides, which can promote both T-helper 1 and 2 responses, curdlan sulfate (CS)–O-(2-hydroxyl)propyl-3-trimethyl ammonium chitosan chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…This observation correlated closely with the reduced lung pathology and the substantial clearance of the virus from the animal lungs. Other polymeric nanoparticles, such as chitosan, a natural polymer composed of randomly distributed β-(1-4)-linked d-glucosamine and N-acetyl-d-glucosamine, and N-(2-hydroxypropyl)methacrylamide/N-isopropylacrylamide (HPMA/NIPAM), were also investigated as intranasal vaccines against respiratory viruses (85)(86)(87)(88)(89)(90)(115)(116)(117)(118)(119)(120)(121). Overall, polymeric nanoparticles have many advantages, including biocompatibility (122), antigen encapsulation and stabilization (123,124), controlled release of antigens and intracellular persistence in APCs (125,126), pathogen-like characteristics, and suitability for intranasal administration (126,127).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…This observation correlated closely with the reduced lung pathology and the substantial clearance of the virus from the animal lungs. Other polymeric nanoparticles, such as chitosan, a natural polymer composed of randomly distributed β-(1-4)-linked d-glucosamine and N-acetyl-d-glucosamine, and N-(2-hydroxypropyl)methacrylamide/N-isopropylacrylamide (HPMA/NIPAM), were also investigated as intranasal vaccines against respiratory viruses (85)(86)(87)(88)(89)(90)(115)(116)(117)(118)(119)(120)(121). Overall, polymeric nanoparticles have many advantages, including biocompatibility (122), antigen encapsulation and stabilization (123,124), controlled release of antigens and intracellular persistence in APCs (125,126), pathogen-like characteristics, and suitability for intranasal administration (126,127).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…The antigen association in the shell of nanocapsules allows a fast recognition by immunocompetent cells and therefore it is expected that it would trigger an efficient immune response. Other nanoformulations have shown similar or lower OVA loading efficiency in comparison to our CSNCs [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 70%
“…Studies by Swaminathan et al, have proved enhanced immune responses by lipid nanoparticle (LNP) adjuvant formulations against ovalbumin (OVA) and hepatitis B virus surface antigen (HBsAg) in BALB/c and C57BL/6 mice injected with HBsAg along with LNPs as compared to HBsAg alone [52] . Co-administration of quarternized chitosan nanoparticles as adjuvants along with ovalbumin intranasally in female BALB/c mice induced activation of APCs followed by enhanced lymphocyte proliferation and differentiation as compared to OVA mixed with aluminum hydroxide gel [53] . Asgary et al, also reported that silver nanoparticles showed increased antibodymediated responses against CVS-11 rabies and reduced toxicity as compared to conventionally used adjuvants such as alum [54] .…”
Section: Nanoparticles As Adjuvants Carriers and Immunogensmentioning
confidence: 97%